2021
DOI: 10.3390/clockssleep3010006
|View full text |Cite
|
Sign up to set email alerts
|

General Anaesthesia Shifts the Murine Circadian Clock in a Time-Dependant Fashion

Abstract: Following general anaesthesia (GA), patients frequently experience sleep disruption and fatigue, which has been hypothesized to result at least in part by GA affecting the circadian clock. Here, we provide the first comprehensive time-dependent analysis of the effects of the commonly administered inhalational anaesthetic, isoflurane, on the murine circadian clock, by analysing its effects on (a) behavioural locomotor rhythms and (b) PER2::LUC expression in the suprachiasmatic nuclei (SCN) of the mouse brain. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The GA-induced shifts shown here (and those in our previous paper [ 9 ]) may be mediated, at least in part, through the activation of different GABA A R subunits or configurations within the SCN. Our demonstration here that three different GABA A R subunits are expressed in the mouse SCN and show strong temporal changes over the course of the day, highlights the complex and dynamic role GABA is likely to play in the central clock.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The GA-induced shifts shown here (and those in our previous paper [ 9 ]) may be mediated, at least in part, through the activation of different GABA A R subunits or configurations within the SCN. Our demonstration here that three different GABA A R subunits are expressed in the mouse SCN and show strong temporal changes over the course of the day, highlights the complex and dynamic role GABA is likely to play in the central clock.…”
Section: Discussionsupporting
confidence: 74%
“…If the mammalian circadian system was shown to respond in a similar manner to GA and light as honey bees, our previous demonstration in bees that the phase shifting effects of isoflurane can be ameliorated by the concurrent administration of light [ 7 ] would provide, at least theoretically, a means to reduce GA-induced phase shifting in mammals. Initial data on the effects of GA on mice in free-running conditions (DD) indicated that, unlike bees, the times of GA-induced phase shifts were not in antiphase to those of light, but occurred at similar circadian times (both GA and light causing delays between CT7 and CT18) [ 9 , 10 ]. The phase response curve presented here for the combined effects of isoflurane (2% for 4 h) and light on behavioural rhythms in mice further these findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations